Efektivitas Teknologi dalam Digital Recruitment untuk Meningkatkan Kualitas Seleksi Karyawan - Wiguna, Wahyu; Ummy Khairani Taringan; Asep Ahmad Rabbany Hidayat; Jerry Enef; Alfia Elzam Zami (IPM2KPE, 2026)
This study aims to analyze the effectiveness of technology in digital recruitment to improve the quality of employee selection, particularly in terms of speed, cost efficiency, assessment accuracy, and candidate experience. The research method used is a literature review, reviewing various scientific sources, journals, and relevant references discussing the application of digital technologies such as online recruitment platforms, Applicant Tracking Systems (ATS), artificial intelligence (AI), data analytics, and video-based interviews in the recruitment and selection process. The results show that the use of digital technology can expand candidate reach, accelerate the selection process, reduce operational costs, minimize subjective bias, and improve the accuracy of matching candidates to organizational needs. Furthermore, the application of AI and data analytics has been shown to increase the accuracy of evaluating candidate competencies and potential, as well as providing a more transparent and positive recruitment experience. The conclusion of this study confirms that the integration of technology in digital recruitment significantly improves the quality of employee selection and provides organizations with a competitive advantage in facing the dynamics of the modern labor market. Keywords: Digital Recruitment, Technology, Employee Selection, Artificial Intelligence